2012
DOI: 10.1002/jbt.21450
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Pyrethroids on Serotonin Release in the Striatum of Awake Rats: An In Vivo Microdialysis Study

Abstract: The present study examined the acute neurotoxic effects of three different pyrethroids, allethrin, cyhalothrin, and deltamethrin on the release of serotonin (5-HT) and its metabolite 5-hydroxyindoleacetic acid (5-HIAA) in the striatum of conscious rats using microdialysis. Allethrin 10 mg/kg reduced extracellular levels of 5-HT to 46%, whereas 20 and 60 mg/kg increased the release to 177% and 243% of baseline, respectively. Cyhalothrin increased 5-HT release to 145–204% and deltamethrin decreased to 58–32% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Indeed, we previously found that the rise in Ca 2þ influx into the SK-N-AS is secondary to the activation of Na þ channels following exposure to deltamethrin (Hossain and Richardson, 2011). Evidence from our microdialysis studies also demonstrate that the inhibition of L-type calcium channel can prevent the Na þ channel-independent effects of pyrethroids on release of extracellular neurotransmitters in rat (Hossain et al, 2013b;Hossain et al, 2006Hossain et al, , 2008. Similarly, Cao et al (2011) showed that deltamethrin potently stimulates calcium influx in cortical neurons and that secondary calcium influx may be mediated by L-type calcium channels or reversal of the Na þ / Ca 2þ exchanger.…”
Section: Discussionsupporting
confidence: 67%
“…Indeed, we previously found that the rise in Ca 2þ influx into the SK-N-AS is secondary to the activation of Na þ channels following exposure to deltamethrin (Hossain and Richardson, 2011). Evidence from our microdialysis studies also demonstrate that the inhibition of L-type calcium channel can prevent the Na þ channel-independent effects of pyrethroids on release of extracellular neurotransmitters in rat (Hossain et al, 2013b;Hossain et al, 2006Hossain et al, , 2008. Similarly, Cao et al (2011) showed that deltamethrin potently stimulates calcium influx in cortical neurons and that secondary calcium influx may be mediated by L-type calcium channels or reversal of the Na þ / Ca 2þ exchanger.…”
Section: Discussionsupporting
confidence: 67%
“…Data analyses. Some developmental effects of DLM were reported previously (Hossain et al, 2013(Hossain et al, , 2015Richardson et al, 2015), therefore, we hypothesized deficits for these outcomes. These data were analyzed using a priori methods.…”
Section: Methodsmentioning
confidence: 92%
“…In addition to alterations in DA biomarkers, Richardson et al (2015) observed deficits in learning, memory, attention, and impulsivity, and increased open-field (OF) activity. By contrast, in adult rats, DLM alters serotonin as well as DA (Hossain et al, 2006(Hossain et al, , 2013. Gestational DLM exposure in rats causes deficits in learning and memory (L&M) when tested at 6-12 weeks of age, alters cholinergic circuitry, increases striatal 3, 4-dihydroxyphenylacetic acid (DOPAC) levels, alters OF activity and rearing, and reduces cytochrome P450s (Aziz et al, 2001;Johri et al, 2006;Lazarini et al, 2001).…”
mentioning
confidence: 99%
“…19 The administration of cyhalothrin to rats at the dose levels of 10, 20 and 60 mg kg −1 caused dose-dependent increases of striatal 5-HT, but no changes were seen in the outflow of 5-HIAA. 20 In a study aimed at determining the effect of permethrin on striatum, median prefrontal cortex and hippocampal monoamine levels, a statistically insignificant increase in 5-HT levels was found in the study group treated with 34 mg kg −1 permethrin, whereas the 5-HIAA levels remained unchanged. 21 There are some studies showing both no change and a decrease in the 5-HT and 5-HIAA levels in the brain following pyrethroid administration.…”
Section: Immunohistochemical Findingsmentioning
confidence: 99%